'Pouring everything that you are': musicians' experiences of optimal performances. Issue 2 (27th July 2020) - Ford, Jessica L.; Vosloo, Justine; Arvinen-Barrow, Monna
Abstract: The purpose of this study was to document the lived experiences of flow during an optimal music performance. Fifteen undergraduate musicians ( M age = 19, 53% male) participated in in-depth, semi-structured interviews, where they were asked to describe an optimal performance experience. Results from an inductive qualitative analysis revealed three main themes: environmental context, emotional connectedness and interpersonal relationships, which synthesised the optimal performance experience. The results also suggest that flow among musicians appears to be a common emotional state and similar to that conceptualised in sport. The ways a musician experiences flow are important, as these can help music educators gain a better understanding of the conceptualisation of flow within music performance. However, given the nuanced differences in the sociocultural environment of a flow experience typical in a sport or music performance, additional research into the divergences of domains may be warranted.